The Study of Epistemological Ambiguities in the Understanding of the “Authoritarian Aspects of Alfarabi’s Political Philosopy” - Babak Omidali (رهیافتهای سیاسی و بین المللی)
In the field of Islamic political philosophy, there is a relatively new interpretation of Alfarabi’s political philosophy that uses the Foucault’s discourse analysis to see unknown aspects of the Alfarabi’s political idea; the aspects that show the historical relationship between “power” and “knowledge” in Muslim societies. Based on this interpretation of the Islamic political knowledge in general and Alfarabi’s idea in particular, we are faced with the “authoritarian” aspects of Alfarabi’s idea of “The Opinions of the People of the Virtuous City”; the idea that arises from the structure of the political power of the Alfarabis’s era, and is formed to expand the hierarchical notion of political order instead of shaping a critical knowledge. In this article, the epistemological foundations of such interpretation are the main issues that will be under discussion in two parts: the “ideological” dimensions of Alfarabi’s political idea and the ways in which Foucault’s discourse analysis can be applied. As far as these issues are concerned, it seems to be some ambiguities in aforementioned interpretation.